The Relationship Between the Use of Injectable Contraceptives and Changes in Body Weight - Subiyatin, Aning; Zulfa, Susan; Hidayati, Elli; Jamil, , Siti (Rajaki of Tulip Medika Publisher, 2024)
Background: Injectable contraception is a contraceptive method made into a liquid and injected into the body. Some contain estrogen and progesterone once a month, but some only contain progesterone every three months. The most frequent side effect of contraception is weight gain. Depo Medroxy Progesterone Acetate (DMPA) stimulates the appetite control center in the hypothalamus, which causes acceptors to overeat. Excessive weight gain causes a number of diseases, such as obesity, hypertension, diabetes, and heart disease.Objective. Purpose : this study aims to analyze the relationship between the provision of injectable contraception and weight changes in PMB